Effectiveness of Smartphone Application â€œNutriatletâ€ in Increasing Energy Intake of Martial Arts Athletes (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
One of the pillars in achieving good sport achievement is athleteâ€™s nutritional status. Preliminary study on martial arts athletes in Student Sport Education and Training Central Office (BPPLOP) of Central Java Province showed that 8% of athletes had malnutrition. Survey of athleteâ€™s consumption showed that average of energy consumption was only 74% from the number of energy requirement. The aim of this study was to test the effectiveness of smartphone application model â€œNutriatletâ€ to increase energy intake of athletes. This study was conducted in 2017 using pre and posttest with control group design. We recruited 30 athletes with 15 athletes in each treatment and control group. Bivariate analysis was performed using cox proportional-hazard test. The output of statistical analysis were p value, median post-intervention duration, and hazard ratio (HR). The analysis was performed using STATA 12.1. The result showed that the athletes which performed dietary planning using Nutriatlet had 4 times higher possibilities to achieve an increase in energy consumption level â‰¥10% per time unit compared to athletes who did not do it.Â